The Impact of Cognitive Reserve in neuropsychological and functional abilities of patients with Alzheimer's disease. A Cross-sectional study. - Sobral, M.; Pestana, M.H.; Paúl, C. (ICAP14-ABS4035, 2013)
Cognitive Reserve (CR) is a hypothetical construct that has been used to inform of cognitive aging and describes the capacity of the adult brain to tolerate the effects of neurodegenerative process. The aim of this work was to determine the association between measures of CR and cognitive and functional ability of Alzheimer´s disease (AD) patients. Methods: Functional and neuropsychological abilities of 75 outpatients with probable AD diagnosis were evaluated. Data collected included sociodemographic and clinical variables. Patients answered two questionnaires, “Participation in leisure activities throughout life” and Cognitive Reserve Questionnaire. The patients completed the Mini-Mental State Examination, Addenbrooke´s Cognitive Examination Revised, Wechsler Adult Intelligence Scale – Third Edition, Clinical Dementia Rating, tests adapted from the Lisbon Battery for Assessment of Dementia and the Barthel Index and the Lawton and Brody’s Index. Results: AD patients with higher CR levels exhibited better scores on cognitive tests than those with lower CR levels. Conclusion: This study showed that patients with high levels of CR may benefit from better results on cognitive tests than other patients with the worst levels of CR after diagnosis of AD.